2017
DOI: 10.1371/journal.pone.0185976
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of peripheral B cells and autoantibodies against the anti-nicotinic acetylcholine receptor derived from patients with myasthenia gravis using single-cell manipulation tools

Abstract: The majority of patients with myasthenia gravis (MG), an organ-specific autoimmune disease, harbor autoantibodies that attack the nicotinic acetylcholine receptor (nAChR-Abs) at the neuromuscular junction of skeletal muscles, resulting in muscle weakness. Single cell manipulation technologies coupled with genetic engineering are very powerful tools to examine T cell and B cell repertoires and the dynamics of adaptive immunity. These tools have been utilized to develop mAbs in parallel with hybridomas, phage di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 68 publications
(102 reference statements)
1
22
0
Order By: Relevance
“…Using in vitro cell culture approaches, it has been demonstrated that B cells expressing AChR autoantibodies exist within the circulation, lymph nodes, and in the bone marrow (44-48). Other studies have identified autoantibody-producing B cells in the circulation through production of recombinant human monoclonal AChR autoantibodies (mAb) from these cells (49).…”
Section: Characterization Of B Cells In Achr Myasthenia Gravismentioning
confidence: 99%
See 2 more Smart Citations
“…Using in vitro cell culture approaches, it has been demonstrated that B cells expressing AChR autoantibodies exist within the circulation, lymph nodes, and in the bone marrow (44-48). Other studies have identified autoantibody-producing B cells in the circulation through production of recombinant human monoclonal AChR autoantibodies (mAb) from these cells (49).…”
Section: Characterization Of B Cells In Achr Myasthenia Gravismentioning
confidence: 99%
“…The first recombinant AChR-specific autoantibodies were cloned from phage display libraries isolated from thymocyte-associated immunoglobulin sequences (31, 43, 50). Several additional AChR-specific human-derived mAbs have been produced using a number of different approaches, including single-cell technology (49). These recombinant human-derived mAbs emulate the properties of AChR autoantibodies found in the serum: They compete for binding to regions of the AChR recognized by serum-derived autoantibodies (50), and they possess pathogenic properties demonstrated through passive transfer of MG (49).…”
Section: Properties Of Achr-specific Autoantibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of their Abs were positive for a cell based assay and they showed pathogenic effects both in vivo and in vitro using the Ab with the highest AChR binding capacity. Intriguingly, more than 50% (between 60% and 100%) of the binding activity of anti-AChR antibodies in the sera of patients with MG was blocked by this monoclonal antibody [18]. These findings suggested the existence of a MIR and could lead to the development of new therapies involving these antibodies [19].…”
Section: Achr Myasthenia Gravismentioning
confidence: 92%
“…According to Sprent (2002), normal expression of nAChR by thymus myoid cells plays an important role in inducing central immune tolerance to muscle proteins of the body (Sprent & Kishimoto, 2002). The certain subunits of AChR were expressed by thymus epithelial cells (Levinson, 2013;Makino et al, 2017;Nakamura et al, 2018). This mechanism is partially controlled by the autoimmune regulator AIRE (Berrih-Aknin, 2014).…”
Section: Introductionmentioning
confidence: 99%